66 Interobserver Variability of Uterine Carcinoma Regarding FIGO Grade, Myometrial Invasion, and Tumor Subtype. (11th January 2018) - Zhang, Songlin; Wang, Xiaohong; Zhu, Hui; Liu, Jing; Yang, Peisha; Buryanek, Jamie; Zhao, Bihong
Abstract: Objectives: Disease prognosis of endometrial carcinoma varies significantly depending on the International Federation of Gynecology and Obstetrics (FIGO) grade, extent of the myometrial invasion, and tumor type. However, assessment of these tumor characteristics can be difficult and subjective. Therefore, the interobserver variability would play a major role in the credibility of the consensus guidelines. Methods: Institutional review board approval was obtained. Five pathologists independently evaluated one representative section of a total of 90 cases of uterine carcinoma for tumor FIGO grade, myometrial invasion, and tumor subtypes. The 90 cases included 73 endometrioid adenocarcinoma, two mixed endometrioid and serous carcinoma, seven carcinosarcoma, six serous carcinoma, and two clear cell carcinoma. Results: For the FIGO grades, only 22/90 cases were agreed on by all five pathologists, 49/90 cases were agreed on by 4/5 pathologists, and 88/90 cases were agreed on by 3/5 pathologists. If the FIGO grades 1 and 2 were together denoted as low grade, and FIGO 3 denoted as high grade, all five pathologists agreed on 70/90 cases. For myometrial invasion (<1/2 vs >1/2), all five pathologists agreed on 65/75 cases, and 4/5 pathologists agreed on 72/75 cases. For carcinoma subtypes, none of the 10 cases of clear cell or serous carcinoma was agreed by all five pathologists based on morphology. Conclusion: Two-tier FIGO grading (low grade vs high grade) appears better than the three-tier classification system, but the group consensus diagnosis seems to be the best system for FIGO grading. Evaluation of myometrial invasion (<1/2 vs >1/2) appears to be very reliable among the practicing pathologists. Identification of the serous or clear cell component based on pure morphology is not reliable, and immunohistochemistry should be routinely applied.